Mortality of emergency general surgical patients and associations with hospital structures and processes. (January 2016) - Ozdemir, B.A.; Sinha, S.; Karthikesalingam, A.; Poloniecki, J.D.; Pearse, R.M.; Grocott, M.P.W.; Thompson, M.M.; Holt, P.J.E.
Abstract: Background: Variations in patient outcomes between providers have been described for emergency admissions, including general surgery. The aim of this study was to investigate whether differences in modifiable hospital structures and processes were associated with variance in mortality, amongst patients admitted for emergency colorectal laparotomy, peptic ulcer surgery, appendicectomy, hernia repair and pancreatitis. Methods: Adult emergency admissions in the English NHS were extracted from the Hospital Episode Statistics between April 2005 and March 2010. The association between mortality and structure and process measures including medical and nursing staffing levels, critical care and operating theatre availability, radiology utilization, teaching hospital status and weekend admissions were investigated. Results: There were 294 602 emergency admissions to 156 NHS Trusts (hospital systems) with a 30-day mortality of 4.2%. Trust-level mortality rates for this cohort ranged from 1.6 to 8.0%. The lowest mortality rates were observed in Trusts with higher levels of medical and nursing staffing, and a greater number of operating theatres and critical care beds relative to provider size. Higher mortality rates were seen in patients admitted to hospital at weekends [OR 1.11 (95% CI 1.06–1.17) P <0.0001], in Trusts with fewer general surgical doctors [1.07 (1.01–1.13) P +0.019] and with lower nursing staff ratios [1.07 (1.01–1.13) P +0.024]. Conclusions: Significant differences between Trusts were identified in staffing and other infrastructure resources for patients admitted with an emergency general surgical diagnosis. Associations between these factors and mortality rates suggest that potentially modifiable factors exist that relate to patient outcomes, and warrant further investigation.